Neurotransmitter release and nerve terminal morphology at the frog neuromuscular junction affected by the dye Erythrosin B - Augustine, George J. (1983)
1. The quantal release of neurotransmitter and the fine structure of frog neuromuscular junctions has been examined in the presence of the xanthene dye Erythrosin B. 2. At concentrations of 10 μM or greater, Erythrosin B produced time- and dose-dependent increases in transmitter release from presynaptic nerve terminals. 3. Miniature end-plate potential (m.e.p.p.) frequency increased in an exponential manner during continuous exposure to the dye. The rate constant for this exponential was dose-dependent, increasing with concentrations from 10 μM to 1 mM. 4. The amplitude of evoked end-plate potentials (e.p.p.s) also increased exponentially during dye treatment, primarily due to an increase in quantal content. Rate constants for this effect were also dose-dependent, and were approximately 1/5 as large as those for m.e.p.p.s. 5. While the frequency of m.e.p.p.s was increasing, their amplitude distribution did not qualitatively change. Thus the dye has little effect on the size of individual quanta. 6. The presynaptic effects of Erythrosin B were irreversible under these experimental conditions. Brief exposure to the dye caused increases in m.e.p.p. frequency and e.p.p. amplitude which were maintained at steady levels during extensive rinsing with dye-free Ringer solution. 7. Prolonged exposure to the dye caused an eventual decrease in m.e.p.p. frequency and abolition of e.p.p.s. Coincident with this decline `giant' m.e.p.p.s as large as 40 mV were observed. 8. At dye concentrations greater than approximately 200 μM, Erythrosin B rapidly and reversibly increased the membrane potential and input resistance of muscle fibres. This post-synaptic effect was small and variable in normal saline, but was pronounced in low potassium solutions. 9. During the period that release was enhanced by Erythrosin B, presynaptic nerve terminals contained the normal complement of synaptic vesicles and other organelles. Mitochondria were swollen in this condition. 10. After m.e.p.p. frequency declined below normal levels and `giant' m.e.p.p.s appeared, the number of synaptic vesicles within nerve terminals declined and dilated cisternae were present. Mitochondria were swollen further. 11. These results do not reveal any mechanism to explain the ability of Erythrosin B to increase transmitter release, but the decline in release may be caused by partial depletion of synaptic vesicles. The `giant' m.e.p.p.s could be due to the discharge of acetylcholine from cisternae.